587 Plasmapheresis in a Patient with “Refractory” Urticarial Vasculitis - Kartal, Ozgur (World Allergy Organization Journal, 2012)
BACKGROUND: Immune complexes have been found in the circulation approximately 30 to 75% of patients with urticarial vasculitis and much evidence supports the role of these immune complexes in the pathogenesis of urticarial vasculitis. Plasmapheresis is effective in removal of these immune complexes. However, few cases have been reported regarding the use of plasmapheresis in the treatment of urticarial vasculitis. METHODS: A 35-year-old woman presented with history of recurrent episodes of generalized painful urticarial plaques often lasting 9 years associated with swelling of her parts of body. Examination revealed multiple urticarial plaques distributed all over the body (particularly in the extremities, palms and soles). The initial laboratory studies, including a complete blood count, thyroid function tests - thyroid autoantibodies, erythrocyte sedimentation rate, hepatitis markers, liver and renal function tests, urinary analysis, stool analysis for parasite ova, total IgE, C3, C4, C1q, CH50, C1 inhibitor levels and antinuclear antibodies were found to be within normal range. Skin prick tests were performed with commonly consumed foods in Turkey found to be negative. A biopsy from an affected area of skin revealed an urticarial vasculitis. Based on the biopsy results, the patient was diagnosed with UV. Treatment with H1/ H2-antihistamines and oral corticosteroids (1 mg/kg/day) had been unsuccessful; therefore hydroxychloroquine 400 mg/day was added. Unfortunately hydroxychloroquine was stopped in the second month due to the emergence of an adverse event (keratopathy). The patient underwent plasma exchange 2 times with an interval of 6 months. Five percent albumin solution as replacement fluid was used. One plasma volume was processed in each session. Apheresis procedure was performed with the “Cell Separator” device. The plasmapheresis procedures were completed without any adverse events. At 13 months after the plasmapheresis, the urticarial plaques were reappeared, but the severity and duration of symptoms were lower than before the plasmapheresis. The newly lesions were re-treated with short-term oral antihistamine regimen. CONCLUSIONS: In conclusion, the presented report supports the usability of plasmapheresis in patients with “refractory” UV. Further clinical studies are needed to confirm our experience.